2022
DOI: 10.1039/d2en00402j
|View full text |Cite
|
Sign up to set email alerts
|

Shape-dependent biological activity of spherical and quasi-spherical silver nanoparticles in E. coli, A549 cells and mice

Abstract: Silver nanoparticles (AgNPs) of various size and shape are widely used because of their antibacterial properties. However, their bioactivity to mammals is insufficiently investigated. The aim of the present study...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 99 publications
0
3
0
Order By: Relevance
“…Previously, we tested the listed methods of application for their ability to reduce copper status indexes. It was found that IP and IV modes of treatment produced the strongest and almost similar effects, but IP mode was less invasive and thus preferable for chronic application [57].…”
Section: Design Of Agnp Treatment Of Mice With Growing Ascitic or Sol...mentioning
confidence: 99%
“…Previously, we tested the listed methods of application for their ability to reduce copper status indexes. It was found that IP and IV modes of treatment produced the strongest and almost similar effects, but IP mode was less invasive and thus preferable for chronic application [57].…”
Section: Design Of Agnp Treatment Of Mice With Growing Ascitic or Sol...mentioning
confidence: 99%
“…Nonetheless, they did not come to any conclusions about how particle shape possibly affected the oral toxicity of AgNPs. Given that different antimicrobial activities have been seen in the spherical, quasi-spherical, and octahedral AgNPs, possibly stemming from their varied facets and surface energy, there is reason to believe that particle shape ought to be responsible for the toxic effects induced by AgNPs in the GIT.…”
Section: Toxicity Mechanisms and Influencing Factors Of Agnps In The Gitmentioning
confidence: 99%
“…Silver nanoparticles are currently demonstrating activity against a wide range of cancer cell lines, including A549, MCF-7, and caco-2, in addition to other types of cancer cell lines [ 9 , 10 ]. This killing efficiency goes back to the small particle size, which facilitates its membrane penetration [ 11 ]. Furthermore, Ag-NPs have recently been discovered to be useful as anti-tumors due to their cytotoxic, antioxidant, and antidiabetic properties, in addition to augmenting the immunogenicity of vaccines and promoting wound and bone healing [ 12 ].…”
Section: Introductionmentioning
confidence: 99%